The nonprofit sector : a research handbook - Powell, Walter W.; Bromley, Patricia (Assistant professor of education) (Stanford, California : Stanford University Press, 2020)
"The third edition of The Nonprofit Sector, this handbook fills a unique space in the nonprofit literature as the only volume aimed at furthering research in the field. Since the last edition, which has remained a core text in the field, the nonprofit sector has evolved and now overlaps to a greater extent with business and government. The third edition highlights the growing role of nonprofits in public policy, current debates over the relationship between nonprofits and democracy, increasingly blurred lines between nonprofits and the market. Themes that remain highly relevant to the field--the history of the sector, the import of religion, the legal treatment of nonprofits--are again taken up in this new edition, but in all new contributions. The third edition features a nearly completely new group of authors. This third edition is not a mere update, but offers readers the cutting-edge of new research on the nonprofit sector"--
Preface -- Acknowledgments -- Introduction. 1. What is the nonprofit sector? / Walter W. Powell -- Part I. Emergence, transformation, and regulation. 2. A history of associational life and the nonprofit sector in the United States / Benjamin Soskis -- 3. Seeing like a philanthropist: from the business of benevolence to the benevolence of business / Aaron Horvath and Walter W. Powell -- 4. The organizational transformation of civil society / Patricia Bromley -- 5. Tangled up in tax: the nonprofit sector and the Federal tax system / Daniel J. Hemel -- Part II. Politics of the public sphere. 6. Political theory and the nonprofit sector / Ted Lechterman and Rob Reich -- 7. Nonprofits as boundary markers: the politics of choice, mobilization, and arbitrage / Elisabeth S. Clemens -- 8. Politics, philanthropy, and inequality / Sarah Reckhow -- Part III. Governance, civic capacity, and communities. 9. Towards a governance framework for government-nonprofit relations / Nicole P. Marwell and Maoz Brown -- 10. Social service nonprofits: navigating conflicting demands / Jennifer E. Mosley -- 11. Nonprofits as urban infrastructure / Christof Brandtner and Claire Dunning -- 12. Immigrant organizations: civic (in)equality and civic (in)visibility / Irene Bloemraad, Shannon Gleeson, and Els de Graauw -- Part IV. Nonprofits, mission, and the market. 13. Economic theories of the social sector: from nonprofits to social enterprise / Maitreesh Ghatak -- 14. Social entrepreneurship: research as disciplined exploration / Johanna Mair -- 15. Nonprofits and the environment: using market forces for social good / Magali A. Delmas, Thomas P. Lyon, and Sean Jackson -- 16. The outcomes movement in philanthropy and the nonprofit sector / Paul Brest -- Part V. Balancing access and inclusion. 17. Charitable nonprofits and the business of health care / Jill R. Horwitz -- 18. Education and the nonprofit sector: schools and organizational intermediaries / Richard Arum and Jacob L. Kepins -- 19. Nonprofit arts organizations: sustainability and rationales for support / Francie Ostrower -- Part VI. Advocacy, engagement, and the public. 20. Advocacy, civic engagement, and social change / David Suárez -- 21. The changing face of nonprofit advocacy: democratizing potentials and risks in an unequal context / Edward T. Walker and Yotala Oszkay -- 22. Advocating for what? The nonprofit press and models of the public / Mike Ananny -- Part VII. Motivation, meaning, and prosocial behavior. 23. What influences charitable giving? / Pamela Paxton -- 24. The altruism budget: measuring and encouraging charitable giving / Laura K. Gee and Jonathan Meer -- 25. What do volunteers do? / Nina Eliasoph -- 26. Religious organizations: crosscutting the nonprofit sector / Brad R. Fulton -- Part VIII. Global and comparative perspectives. 27. The global rise of nongovernmental organizations / Evan Schofer and Wesley Longhofer -- 28. Global backlash against foreign funding to domestic nongovernmental organizations / Kendra Dupuy and Aseem Prakash -- 29. Social movements in a global context: history, content, and form / Breno Bringel and Elizabeth McKenna -- 30. Comparative nonprofit sector research: a critical assessment / Helmut K. Anheier, Markus Lang, and Stefan Toepler -- Notes -- References -- Contributors -- Index.
Includes bibliographical references (pages 703-844) and index.
Online resource; title from PDF title page (Ebook Central, viewed September 11, 2020).
eBooks on EBSCOhost
Keywords: Nonprofit organizations -- Management; Nonprofit organizations; Charitable uses, trusts, and foundations; Organizations, Nonprofit; Associations sans but lucratif -- Gestion; Associations sans but lucratif; Fondations (Droit); nonprofit organizations; Charitable uses, trusts, and foundations; Nonprofit organizations; Nonprofit organizations -- Management